2022
DOI: 10.1609/hcomp.v10i1.22002
|View full text |Cite
|
Sign up to set email alerts
|

HSI: Human Saliency Imitator for Benchmarking Saliency-Based Model Explanations

Abstract: Model explanations are generated by XAI (explainable AI) methods to help people understand and interpret machine learning models. To study XAI methods from the human perspective, we propose a human-based benchmark dataset, i.e., human saliency benchmark (HSB), for evaluating saliency-based XAI methods. Different from existing human saliency annotations where class-related features are manually and subjectively labeled, this benchmark collects more objective human attention on vision information with a precise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Typically, the similarity between human and CNN attention maps is quite low [10, [47][48][49][50]. Human attention tends to be more selective and focused on specific areas, while CNN attention is more diffuse and distributed [50,51]. Some studies found that CNN put more weight on context than humans [9,11].…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Typically, the similarity between human and CNN attention maps is quite low [10, [47][48][49][50]. Human attention tends to be more selective and focused on specific areas, while CNN attention is more diffuse and distributed [50,51]. Some studies found that CNN put more weight on context than humans [9,11].…”
Section: Overview Of Findingsmentioning
confidence: 99%
“…For instance, similarity is higher for deeper networks with more layers [9] and for networks that process information more like humans, for instance via biologically plausible receptive fields [10] or human-inspired attention mechanisms [47,53]. A second technological influence on human-CNN similarity is the XAI method used to elicit CNN attention maps [8,49,51,54]. This is not surprising, given the immense variety in the outputs of different XAI methods: some highlight edges while others highlight broad regions and some provide pixelated or patch-like segments while others provide smooth and gradual heatmaps.…”
Section: Overview Of Findingsmentioning
confidence: 99%
See 3 more Smart Citations